Effects of endophytic Beauveria bassiana (Ascomycota: Hypocreales) on biological and reproductive parameters and food preference of the soybean pest Helicoverpa gelotopoeon - Russo, María Leticia (2019)
Objectives: We studied Beauveria bassiana ability to endophytic colonize soybean and its effects on some biological and reproductive parameters and on the food preference of Helicoverpa gelotopoeon, a polyphagous plague of several agronomic crops. Methods: A suspension of 1x108 conidia ml-1 of B. bassiana (LPSC 1098), was inoculated in soybean plants using the leaf spraying method. H. gelotopoeon survival, developement, fecundity and fertility were registered to evaluate fungal effect. Also, food preference was determined by the free-choice method. Results: B. bassiana as an endophyte adversely affected the duration of the larval stages (L1, L2, L3, L4) and of the adult stages, as well as the total duration of the life cycle. Furthermore, the oviposition period, fecundity and fertility of H. gelotopoeon decreased. This is the first report of decreased consumption of soybean leaves by H. gelotopoeon due to endophytic B. bassiana. Conclusions: This investigation shows that endophytic fungi could be considered as useful microorganisms for the integrated pest management